STUDENTS' PROFICIENCY IN IDENTIFYING PRONOUNS IN ENGLISH SENTENCES: A STUDY OF SMA SWASTA CERDAS BANGSA - Perangin-angin, Sempa; Lestari, Triana; Puspita, Clara; Umami, Risa; Panggabean, Edward; Efrizah, Doni (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Many students struggle to identify pronouns in sentences, a critical aspect of English grammar necessary for constructing clear and coherent communication. Pronouns play a vital role in sentence structure by replacing nouns to avoid redundancy, yet their correct usage poses challenges for learners. This study investigates the proficiency of tenth-grade students at SMA Swasta Cerdas Bangsa in identifying pronouns in English sentences and explores the specific difficulties they face. The research aimed to evaluate students' ability to recognize different types of pronouns and pinpoint areas requiring instructional support. Adopting a case study methodology, the study collected data from 30 students in class X.1 through a 30-item test consisting of multiple-choice and fill-in-the-blank questions. Results showed that only 41% of the students correctly identified pronouns, with common challenges including confusion in pronoun selection and insufficient understanding of pronoun usage. These findings highlight the need for targeted teaching strategies, such as explicit grammar instruction and contextualized exercises, to enhance students' grammatical competence and overall language proficiency.